In-silico ANALYSIS OF PHYTOCHEMICALS FROM Linum usitatissimum AGAINST Staphylococcus aureus CAUSING ECZEMA - ROUTRAY, ATASI; SETHI, PRAJNA PRIYADARSINI; SAMAL, RUNKI PRIYADARSINI; PANDEY, MUKUNDJEE; BHATTACHARYAY, DIPANKAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Eczema is caused by “Staphylococcus aureus”. Aspatate semialdehyde “dehydrogenase” is one of its major enzyme. Linum usitatissimum is known to cure eczema. The plant extract contains different phytochemical compounds. By using “Biovia Discovery Studio”, “molecular docking” of the phytochemicals with the enzymes was studied. The results showed that Linum usitatissimum can deactivate the aspatate semialdehyde dehydrogenase enzyme in that way interrupting the microbe’s life cycle.